Bioactive Organocopper Compound from Pseudomonas aeruginosa Inhibits the Growth of Xanthomonas citri subsp. citri - de Oliveira, Admilton G.; Spago, Flavia R.; Simionato, Ane S.; Navarro, Miguel O. P.; da Silva, Caroline S.; Barazetti, André R.; Cely, Martha V. T.; Tischer, Cesar A.; San Martin, Juca A. B.; de Jesus Andrade, Célia G. T.; Novello, Cláudio R.; Mello, João C. P.; et al. (Frontiers in Microbiology, 2016)
Citrus canker is a very destructive disease of citrus species. The challenge is to find new compounds that show strong antibiotic activity and low toxicity to plants and the environment. The objectives of the present study were (1) to extract, purify and evaluate the secondary metabolites with antibiotic activity produced by Pseudomonas aeruginosa LV strain in vitro against Xanthomonas citri subsp. citri (strain 306), (2) to determine the potential of semi-purified secondary metabolites in foliar application to control citrus canker under greenhouse conditions, and (3) to identify antibiotic activity in orange leaf mesophyll infected with strain 306, by electron microscopy. Two pure bioactive compounds were isolated, an organocopper antibiotic compound (OAC) and phenazine-1-carboxamide. Phenazine-1-carboxamide did not show any antibiotic activity under the experimental conditions used in this study. The OAC showed a high level of antibiotic activity with a minimum inhibitory concentration of 0.12 μg mL-1. In greenhouse tests for control of citrus canker in orange trees, the semi-purified fraction F3d reduced lesion formation by about 97%. The concentration used was 500 times lower than that for the recommended commercial copper-based product. Electron microscopy showed that F3d altered the exopolysaccharide matrix and caused cell lysis of the pathogen inside the citrus canker lesions. These results suggest that secondary metabolites produced by inducing P. aeruginosa LV strain have a high potential to be used as a bioproduct to control citrus canker.